Governance and subjective well-being in the Countries of the Andean Community (CAN) - Núñez-Naranjo, Aracelly Fernanda; Morales-Urrutia, Ximena; Martínez-Jumbo, Ariel (Heritage and Sustainable Development, 2024)
This study presents an analysis of the relationship between governance and subjective well-being in the Andean Community of Nations. The analyzed data is sourced from the World Values Survey of Wave 7. A quantitative approach was employed to investigate perceptions and political attitudes in the region. It highlights a positive, albeit slight, connection between subjective well-being and governmental trust, along with the positive influence of perception on wealth redistribution in well-being. Despite receiving subsidies, the unemployed consistently exhibit lower satisfaction levels. Significant associations were identified between governmental trust and opinions on wealth redistribution and surveillance. Additionally, political interest is positively correlated with the preference for men to excel in politics, indicating disparities in attitudes toward gender equality. These findings underscore the complex interaction between governance, well-being, and political perceptions in the Andean region.